Active techniques in the meaningful learning of english language for primary school students of the seventh grades at International Bilingual Educational Center CEBI in Ambato City during the first term of school year 2008 - 2009 - Salazar Paredes, Cristina Elizabeth (2009)
To develop this research, the scheme proposed by the Army Polytechnic School´s Language Department has been followed in detail. It clearly shows us how to develop a research and our dear Tutors helped us to obtain the requirement results which permit us to complete it successfully. This research focused on the use of Active Techniques in order to achieve Meaningful Learning of English Language for the Primary School´s Students of the Seventh Grades at International Bilingual Educational Center CEBI in Ambato city during the first term of school year 2008 2009. Dependent and Independent variables were determined and categorized in the theoretical frame to obtain the main items through the interview, which allowed to get the required information to set up a proposal. The analysis and interpretation of the outcomes were used to set up the conclusions and recommendations, directly based of the specific objectives which were established at the beginning of the research work. This work is supported on the application of methodological resources of the modern and critical didactics of language, which will allow the development of skills, waking up the interest for meaningful learning in a cooperative, reflexive and social environment, through the seek of a whole education since the acquisition of a language contributes to the interpersonal communication.